How Digital Empowerment Promotes Rural Autonomous Governance? — A Case Study of Houwei Village, Xingdian Street, Pukou District, Nanjing - Li Xiu; Yang Zhixuan; Liu Yinglu (E3S Web of Conferences)
This paper uses Houwei Village, Xingdian Street, Pukou District, Nanjing, as a case study to explore how agricultural IoT, smart community services, and e-commerce platforms empower rural governance and enhance villagers' subjectivity and governance effectiveness. By leveraging these digital tools, the paper also examines their contribution to building sustainable rural communities, in line with the global goal of promoting sustainable cities and communities.